2015
DOI: 10.1016/j.drugalcdep.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alcohol consumption: United States, 2001–2002 to 2012–2013

Abstract: Background-Documenting changes in alcohol consumption is critical for assessing future health service and alcohol treatment needs, evaluating efforts to modify drinking behavior and understanding the impact of shifting demographics and social norms. For the period since the year 2000, published data on drinking trends have been scarce and inconsistent.Methods-Using data from two large, nationally representative surveys of U.S. adults (2001-2002 and 2012-2013) that contained virtually identical questions on con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
191
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(206 citation statements)
references
References 15 publications
11
191
1
3
Order By: Relevance
“…A prevalência do consumo abusivo de álcool no Brasil é similar àquelas reportadas em diferentes países do mundo, indicando alta prevalência, padrão de ocorrência maior entre os homens, entre os indivíduos mais jovens e entre aqueles com melhor nível socioeconômico e maior escolaridade 2 . Nos Estados Unidos, Dawson et al 9 10 . Não foram identificadas na literatura explicações para o aumento do consumo abusivo de álcool entre os indivíduos com maior idade.…”
Section: Tabelaunclassified
“…A prevalência do consumo abusivo de álcool no Brasil é similar àquelas reportadas em diferentes países do mundo, indicando alta prevalência, padrão de ocorrência maior entre os homens, entre os indivíduos mais jovens e entre aqueles com melhor nível socioeconômico e maior escolaridade 2 . Nos Estados Unidos, Dawson et al 9 10 . Não foram identificadas na literatura explicações para o aumento do consumo abusivo de álcool entre os indivíduos com maior idade.…”
Section: Tabelaunclassified
“…Alcoholic beverages are by far the most commonly used and abused of psychoactive substances, and alcohol use has increased over the past decade (Dawson, Goldstein, Saha, & Grant, 2015). According to the 2013 National Survey on Drug Use and Health (SAMHSA, 2014), more than 60 million individuals aged 12 years and older in the United States are estimated to have engaged in past-month binge drinking, and an estimated 16.5 million Americans have engaged in heavy drinking.…”
Section: The Challenge Is Large Important and Compellingmentioning
confidence: 99%
“…In wave 4 of the NEXT Generation Study, 50% of respondents reported that they first became drunk within 1 year of the age they started to drink. In the National Epidemiologic Study of Alcoholism and Related Conditions III [18] (n = 36 083; age 18+ interviewed face-to-face), two-thirds of respondents who started drinking before age 21 reported being drunk within a year of their first drink.…”
Section: The Usefulness Of 'Age At First Drink' As a Concept In Alcohmentioning
confidence: 99%